(3GdLGeY GdUZjQ aj GdfMhs - (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, J (B761 (3g` s ((3eMeO Hf eMeO GdeYQha s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdcdeI bhd eaQO (B: (3hgj GSe haYd hMQa aGdGSe cdeI JOd Ydi eYfi s
(3BNQgG (B:s
(3hjLH ai de jYjg hj heLF eg aQZ ef Jfejbg s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3YdjgG ebGHdI HNW GdfGSN faSg ef fSNI ecJhHI ef fSNI HNW GdTjN jGSjf GdPi cJH GdCUd hMhGT GdcJGH hJGQjN GdebGHdI SfI (B1109 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B/ (3HYKJ GdSYhOjI (B((3fMh (B39) s
Keywords: (3GdfMhs